Secret santa: anonymity, signaling, and conditional cooperation - David Hugh-Jones; David Reinstein (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
Costly signaling of commitment to a group has been proposed as an explanation for participation in religion and ritual. But if the signal’s cost is too small, freeriders will send the signal and behave selfishly later. Effective signaling may then be prohibitively costly. If the average level of signaling in a group is observable, but individual effort is not, then freeriders can behave selfishly without being detected, and group members will learn about the average level of commitment among the group. We develop a formal model, and give examples of institutions that enable anonymous signaling, including ritual, religion, music and dance, voting, charitable donations, and military institutions. We explore the value of anonymity in the laboratory with a repeated two-stage public goods game with exclusion. When first-stage contributions are anonymous, subjects are better at predicting second-stage behavior, and maintain a substantially higher level of cooperation.
Keywords: H41; 330; signaling; anonymity; public goods; Öffentliches Gut; Wiederholte Spiele; Trittbrettfahrerverhalten; Signalling; Soziale Gruppe; Kooperation; Test